Kontribusi Minat Belajar Dan Persepsi Siswa Tentang Kinerja Guru Terhadap Prestasi Belajar Matematika Di SD Muhammadiyah 14 Surakarta Tahun Ajaran 2016/2017 - Saputro, Bagas, Drs. Saring Marsudi, SH. M.Pd (2017)
The purpose of this study is to determine: 1) Contribution of learning interest in mathematics achievement; 2) The contribution of students perceptions of teacher performance in mathematics achievement; 3) Contribution of learning interest and student's perceptions of teacher performance linearly on mathematics achievement. This research is quantitative study using survey research design. The objective of this study is all high-grade students at SD Muhammadiyah Surakarta 14 in academic year 2016/2017, the number of students are 84. The sample is taken from 46 students by using the solvin's formula. The required data is achieved through a questionnaire, and documentation. Previously questionnaire is tested then the validity and reliability also are tested. The data analysis technique used multiple linear regression analysis, t test, F test, test R^2, and the relative contribution and effective. The conclusions of this research are: 1) learning interest has contributed 6.828 to the value of the probability of 0.000. 2) Student perceptions of teacher performance have contributed 3.716 to the probability of a value of 0.001. 3) Both of learning interest and student perceptions of teacher performance have contributed to mathematics achievement, it is support from the results of the regression analysis achieved F test to 37.153 accepted at significance level of 5%. The Big contribution of variable learning interest and student perceptions of teacher performance in the mathematics achievement is 63.3%, whereas the remaining 36.7% is influenced by other variables.